Black phosphorus-based van der Waals heterostructures for mid-infrared light-emission applications - Zong, Xinrong (2021)
Mid-infrared (MIR) light-emitting devices play a key role in optical communications, thermal imaging, and material analysis applications. Two-dimensional (2D) materials offer a promising direction for next-generation MIR devices owing to their exotic optical properties, as well as the ultimate thickness limit. More importantly, van der Waals heterostructures-combining the best of various 2D materials at an artificial atomic level-provide many new possibilities for constructing MIR light-emitting devices of large tuneability and high integration. Here, we introduce a simple but novel van der Waals heterostructure for MIR light-emission applications built from thin-film BP and transition metal dichalcogenides (TMDCs), in which BP acts as an MIR light-emission layer. For BP-WSe2 heterostructures, an enhancement of ~200% in the photoluminescence intensities in the MIR region is observed, demonstrating highly efficient energy transfer in this heterostructure with type-I band alignment. For BP-MoS2 heterostructures, a room temperature MIR light-emitting diode (LED) is enabled through the formation of a vertical PN heterojunction at the interface. Our work reveals that the BP-TMDC heterostructure with efficient light emission in the MIR range, either optically or electrically activated, provides a promising platform for infrared light property studies and applications.